Public Interest in Population Genetic Screening for Cancer Risk - Roberts, Megan C.; Foss, Kimberly S.; Henderson, Gail E.; Powell, Sabrina N.; Saylor, Katherine W.; Weck, Karen E.; Milko, Laura V. (Frontiers in Genetics, 2022)
An emerging role for DNA sequencing is to identify people at risk for an inherited cancer syndrome in order to prevent or ameliorate the manifestation of symptoms. Two cancer syndromes, Hereditary Breast and Ovarian Cancer and Lynch Syndrome meet the “Tier 1” evidence threshold established by the Centers for Disease Control and Prevention (CDC) for routine testing of patients with a personal or family history of cancer. Advancements in genomic medicine have accelerated public health pilot programs for genomic screening of all adults for highly medically actionable conditions such as the Tier 1 conditions. However, inadequate evidence to support population genomic screening (PGS) has delayed widespread adoption. Understanding factors that impact public awareness of and interest in PGS, will enhance effective and equitable uptake. We present the results of 746 healthy adults surveyed about their awareness of genetic testing, their interest in learning their cancer risk, and likelihood of participating in a PGS test. Approximately half the respondents were aware of genetic testing for inherited cancer risk and would choose to learn their cancer risk. A sizeable majority of the respondents who were interested in learning their cancer risk also said they were likely to participate in a PGS test that involved a clinical appointment and blood draw, but no out-of-pocket cost. Our results suggest that engaging and educating the general population about the benefits of learning about an inherited cancer predisposition may be an important strategy to address recruitment barriers to PGS.